Development of the ecological culture of future teachers by improving the quality of Education (“On the example of the science” the newest history of Uzbekistan)” - Ismoilova Gulbakhor Azamovna; Muxammedova Mohichexra Baxodir qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with reforming our national education system, improving the quality of education, training creative teachers with the skills and qualifications to apply modern pedagogical and information technologies in practice.